2016
DOI: 10.1088/1757-899x/132/1/012029
|View full text |Cite
|
Sign up to set email alerts
|

Calibration Interval Adjustment of a Measuring Instrument in Industries During Long-term Use

Abstract: Abstract. Calibration interval adjustment of measuring instruments is one of the urgent tasks in industries. The article represents the calibration interval calculation of the potentiometer PCB-4P according to the verifications for the 4 year period of the Metrological Department in the aviation plant. The calibration interval is shown to be increased according to the calculation of its reliability and stability of metrological characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…Besides, as shown previously [6][7][8], the magnetic flux density also depends on the pole pairs number of the magnetic system. Also in [6] it is indicated that for a given tape width the value of the double integral ) , , ( 0 I y x D remains practically constant when the pairs of poles number of the magnetic system changes.…”
Section: Resultssupporting
confidence: 57%
“…Besides, as shown previously [6][7][8], the magnetic flux density also depends on the pole pairs number of the magnetic system. Also in [6] it is indicated that for a given tape width the value of the double integral ) , , ( 0 I y x D remains practically constant when the pairs of poles number of the magnetic system changes.…”
Section: Resultssupporting
confidence: 57%
“…Optimal calibration intervals are those which can be established to provide measurement reliability objectives in maximum periods between adjacent calibrations. The process for determination of optimal interval is a statistical process, requiring accurate and sufficient data taken during the monitoring of equipment behavior [9], [11]- [13].…”
Section: Determination Of the Optimal Calibration Intervalmentioning
confidence: 99%
“…There appears to be no universally applicable single best practice for establishing and adjusting the calibration intervals, which is why every laboratory needs to be familiar with its equipment measuring parameters and understand the calibration interval determination process. Also, for the range of measuring instruments, no single method is ideally suited [4], [11]- [13].…”
Section: Determination Of the Optimal Calibration Intervalmentioning
confidence: 99%
See 1 more Smart Citation
“…A method of measurements by comparison against an actual measure is commonly used providing a comparison of the value to be measured u x (t) and the value of calibration signal u 0 (t) reproduced by measure. The practical implementation of this method including bridge and differentiation circuits requires the availability of high-sensitivity comparators possessing a resolution that, in large part, defines the uncertainty of measurements [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%